Comparison Between Clonazepam and Bromazepam as Premedication Drugs to Reduce Anxiety in Patients Undergoing Elective Surgery Under General Anaesthesia (KYAMC Journal, 2022)
Background: The majority of patients admitted in hospital for elective surgery experience anxiety preoperatively which can adversely influence the surgical procedure as well as the patient’s recovery. Reduction of anxiety and fear during preoperative period in patients of elective surgery is an essential surgical preparation. Benzodiazepines are the most commonly used drugs for this purpose.Materials and Methods: The study was carried out in a series of 60 consecutive, randomly selected patients, aged 18-60 years, admitted for elective surgery under General Anaesthesia, in Combined Military Hospital, Chattogram during the period September 2021 to February 2022. Patients who received Clonazepam or Bromazepam as preoperative medication were included in the study. Anxiety was scored using VAS (Visual Analogue Scale), sedation was scored by using Ramsay Sedation Scale and anterograde amnesia by asking preoperative events after 24 hours of premedication.Results: While evaluating mean anxiety reduction, mean reduction is not significantly different between the two groups (P value 0.856). Sedation level was more achieved with Clonazepam but that was not statistically significant (mean 2.13 vs mean 2.0, P value 0.557). In the Clonazepam group, greater percentage of patients could not recall preoperative events but that was not statistically significant (average 51.10% vs 39.99%, P value>0.05). Incidence of adverse effects was more in the Bromazepam group (16.66% vs 6.66%).Conclusion: The standard administration of Clonazepam and Bromazepam before operation provides patients with a moderate reduction of periprocedural anxiety. Clonazepam produces more amnesia, sedation and less adverse effects.. Therefore, this study favors routine use of Clonazepam as premedication to reduce anxiety before surgery.KYAMC Journal Vol. 13, No. 03, October 2022: 139-144